2009
DOI: 10.1111/j.1365-2966.2009.14640.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of long-term superorbital periodicities in the pseudo-transient LMXBs: IGR J17098−3628 and EXO 0748−676

Abstract: Long‐term monitoring of the recently discovered X‐ray transient, IGR J17098−3628, by the All‐Sky Monitor on‐board the Rossi X‐Ray Timing Explorer, has shown that it displays a long‐term (≈163 d) quasi‐periodic modulation in the data spanning its ‘active’ state (i.e. approximately MJD 53450–54200). Furthermore, this light curve is not typical of ‘classical’ soft X‐ray transients, in that J17098−3628 has remained active since its initial discovery, and may be more akin to the pseudo‐transient EXO 0748−676, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A P sup of 163 d was detected during the higher state in this quasi‐persistent LMXB. It is clearly not stable and shows steady evolution with several significant detected signals in the DPS during the portions of the higher state where the previously published superorbital periods were noted (Kotze et al 2009). There is no evidence for periodic signals in the low state.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A P sup of 163 d was detected during the higher state in this quasi‐persistent LMXB. It is clearly not stable and shows steady evolution with several significant detected signals in the DPS during the portions of the higher state where the previously published superorbital periods were noted (Kotze et al 2009). There is no evidence for periodic signals in the low state.…”
Section: Discussionmentioning
confidence: 71%
“…IGR J17098−3628 has an unknown location on Fig. 1, but in Kotze et al (2009) we argued that, based on the apparent similarities with EXO 0748−676, IGR J17098−3628 likely also has P orb < 1 d. As an LMXB with P orb < 1 d, IGR J17098−3628 would not be expected to produce steadily precessing warped accretion discs (OD01).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As of the date of the present work, the source reached about two years of activity. In spite of the long duration, it is not the longest outburst ever seen from a transient BHC (see for example the nearby X-ray transient IGR J17098-3628 [14]). Are these changes in IGR J17091-3624 behaviour representing an evolution from a transient source to a persistent one as happened for GRS 1915+105?…”
Section: Discussionmentioning
confidence: 99%
“…Although Ogilvie and Dubus (2001) showed that not all LMXBs are likely to experience warping, there is strong observational evidence in our case for some form of disk structures that must be present above the disk plane. Kotze et al (2009) analyzed the long term RXTE ASM light curve of EXO 0748-676 and carried out a period search using the Lomb Scargle method and reported a super-orbital period corresponding to 180.8±0.3 d during the "active" state. They interpret this super-orbital periodicity as a consequence of coupled precessional and warping effects.…”
Section: Irradiation Induced Vertical Structuresmentioning
confidence: 99%